Takaful participation readiness model (TPRM): the influence of takaful knowledge, religious commitment and materialism with the moderating effect of switching costs / Hartini Ab Ghani - Ab Ghani, Hartini (Institute of Graduate Studies, UiTM, 2017)
Takaful (Islamic Insurance) was introduced in Malaysia to provide a better alternative for Muslims. As Muslims are known to be very concerned with religious obligation, family Takaful, thus, should be the life insurance coverage of choice. However, despite the obligation of having family Takaful and Muslim is the predominant religion in Malaysia, the penetration rate of family Takaful in 2013 was only 14 percent as compared to conventional life insurance of 55 percent. It is therefore essential to investigate the factors causing or inhibiting the low penetration rate. Past studies have shown that switching costs are among the contemporary issues in explaining consumer behaviour. The effect of switching costs, however, has never been tested in the area of Takaful. The objective of this study is therefore to empirically test the relationship between switching costs and behavioural intention of the Malay professional conventional policyholders, leading to advancing a Takaful Participation Readiness Model (TPRM).